KEDUDUKAN ISTIṢHĀB SEBAGAI ARGUMENTASI HUKUM ISLAM DAN PENGARUHNYA TERHADAP PERSOALAN FURU’IYAH - Ikhsan, Muhammad; Azwar, Azwar; Yunus, Imran Muhammad (JURNAL HAKAM, 2024)
This research aims to describe the views of Ulama regarding the blasphemy of istiṣhāb and its influence on furū'iyah issues in Islamic jurisprudence. This research uses a descriptive-qualitative method with a uṣūl fiqh and historical approach. The results of the research show that: first, in addressing whether istiṣhāb can be used as a proof in the process of determining a law or not, Uṣūl Fiqh scholars are divided into three opinions, namely the opinion which states that istiṣhāb is a proof (hujjah) in determining or disproving a law; the opinion which states that istiṣhāb cannot be used as an absolute proof, either in establishing the law or denying it; and the opinion which chooses that istiṣhāb is a proof when refuting people who view past legal changes—or what is known as bara'ah al-żimmah—and cannot be used as evidence to establish a new law. Second, if we look further into the discussion and study of Islamic Jurisprudence, it is found that there are many furū'iyah issues discussed by the jurists who then use istiṣhāb as one of their foundations or foundations in holding a madhhab or opinion. Regarding some of these problems, the ulama then differed in their judgments because of differences in ijtihad through istiṣhāb.